2018
DOI: 10.1186/s12957-018-1523-2
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate preoperative membranous urethral length predicts recovery of urinary continence after robot-assisted laparoscopic prostatectomy

Abstract: PurposeWe investigated that preoperative membranous urethral length (MUL) would be associated with the recovery of urinary continence after robot-assisted laparoscopic prostatectomy (RALP).Patients and methodsWe studied 204 patients who underwent RALP between May 2013 and March 2016. All patients underwent pelvic magnetic resonance imaging (MRI) preoperatively to measure MUL. Urinary continence was defined as the use of one pad or less (safety pad). The 204 patients were divided into two groups: continence gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
3
31
0
2
Order By: Relevance
“…This is consistent with our meta-analysis. Ikarashi et al reported a study that included 204 patients who underwent RALP and suggested that a preoperative membranous urethral length > 12 mm (after performing ROC analysis) was an independent predictor of postoperative urinary continence (at the 12-month follow-up) after multivariate analysis (p = 0.026) [20]. Porpiglia et al reported a study involving 252 patients and indicated that the continence rate was 98.0% after catheter removal 24 wk.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our meta-analysis. Ikarashi et al reported a study that included 204 patients who underwent RALP and suggested that a preoperative membranous urethral length > 12 mm (after performing ROC analysis) was an independent predictor of postoperative urinary continence (at the 12-month follow-up) after multivariate analysis (p = 0.026) [20]. Porpiglia et al reported a study involving 252 patients and indicated that the continence rate was 98.0% after catheter removal 24 wk.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that may affect postoperative short-and long-term continence rates include the following: severity of preoperative lower urinary tract symptoms (10); presence of preoperative erectile dysfunction (11); preoperative membranous urethra length, measured by T2-weighted magnetic resonance images (10,12); presence of a median lobe (13); previous transurethral resection of the prostate (14); prostate cancer treatment (15); bony pelvic dimensions (16); cigarette smoking at the time of surgery (6); and type 2 diabetes mellitus (17).…”
Section: Preoperative Factors That Affect Continence Ratesmentioning
confidence: 99%
“…The sphincter length, which is probably directly related to faster and more reliable continence recovery after RP, can be quantified by measurements with MRI [11,12]. Ikarashi et al [13] suggested a 12-mm cutoff value of the membranous urethral length, while Rico et al [14] set it at 10 mm. Nevertheless, in most studies, measurements have been made both prior to the procedure and retrospectively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ikarashi et al [13] suggested a 12-mm cutoff value of the membranous urethral length, while Rico et al [14] set it at 10 mm. Nevertheless, in most studies, measurements have been made both prior to the procedure and retrospectively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%